Penerapan Zero Runoff System (ZROS) dan Efektivitas Penurunan Limpasan Permukaan Pada Lahan Miring di DAS Cidanau, Banten - Wirasembada, Yanuar Chandra; Setiawan, Budi Indra; Saptomo, Satyanto Krido (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Runoff is one of flood and erosion causal factor in Indonesia. Runoff occurred when rainfall cannot be infiltrated and flowed on the ground surface. Cidanau watershed has quite high rainfall average (2573 mm/year) so it has high runoff potential. Zero Runoff System (ZROS) is one of water conservation way which can infiltrate runoff to the ground using permeation structures. ZROS’s successful parameter in order to decreasing runoff rate can be observed by the soil water content differences before and after ZROS application. Soil water content estimation was conducted by water balance model with and without runoff and then it is compared with soil water content from measuring. The simulation results indicated that soil water content in the research field before and after ZROS application is 0.476 and 0.569 m3/m3 respectively. The simulation is also conducted for past 10 years (2004-2013) and resulted higher soil water content if ZROS were applied. This results indicates that ZROS capable to decrease and permeate runoff to the ground and then increase soil water content level. Water balance model with and without runoff has coefficient of determination (R2) 0.606. It means that this model could simulate the soil water content differences before and after ZROS application valid relatively.